2023
DOI: 10.1021/acs.jafc.2c08612
|View full text |Cite
|
Sign up to set email alerts
|

Eco-Oriented Formulation and Stabilization of Oil–Colloidal Biodelivery Systems Based on GC-MS/MS-Profiled Phytochemicals from Wild Tomato for Long-Term Retention and Penetration on Applied Surfaces for Effective Crop Protection

Abstract: Vegetable oils as hydrophobic reserves in oil dispersions (OD) provide a practical approach to halt bioactive degradation for user and environment-efficient pest management. Using biodegradable soybean oil (57%), castor oil ethoxylate (5%), calcium dodecyl benzenesulfonates as nonionic and an-ionic surfactants, bentonite (2%), and fumed silica as rheology modifiers, we created an oil−colloidal biodelivery sytem (30%) of tomato extract with homogenization. The quality-influencing parameters, such as particle si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 56 publications
(101 reference statements)
1
8
0
Order By: Relevance
“…Higher pH values result in settling particles forming rougher masses, which settle more quickly from the tube’s top to its bottom. The findings are consistent with earlier research, which found that acidity or alkalinity changed at a far slower rate during storage …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Higher pH values result in settling particles forming rougher masses, which settle more quickly from the tube’s top to its bottom. The findings are consistent with earlier research, which found that acidity or alkalinity changed at a far slower rate during storage …”
Section: Resultssupporting
confidence: 93%
“…Safety Evaluation of Cotton. NS and SC solutions were used to soak appropriate numbers (10) of seeds of uniform size and fullness at various doses (0.5, 5, 50, and 500 mg L −1 ), whereas the control group received the same treatment with deionized water. The seeds were put in filter paper-lined Petri dishes (9 cm in diameter) with 10 seeds per group and three duplicates after soaking for 24 h at 25 °C.…”
Section: Residual Dynamicsmentioning
confidence: 99%
“…13 Other researchers are developing novel and greener pesticide delivery approaches such as the use of wild tomato (Solanum pimpinellifolium) leaf extracts for aphid control in a vegetable oil dispersion formulation. 14 Other factors may create postharvest losses like mycotoxin contamination. Antagonistic yeasts are being examined as a biological control method to degrade mycotoxins.…”
mentioning
confidence: 99%
“…For example, an exploration of CuO nanoparticles for disease suppression in tomato found that negatively charged particles were absorbed more effectively into leaf surfaces and reduced disease levels as compared to positively charged particles . Other researchers are developing novel and greener pesticide delivery approaches such as the use of wild tomato ( Solanum pimpinellifolium ) leaf extracts for aphid control in a vegetable oil dispersion formulation . Other factors may create postharvest losses like mycotoxin contamination.…”
mentioning
confidence: 99%
See 1 more Smart Citation